Peran Guru dalam Membentuk Karakter Disiplin Peserta Didik Terhadap Tata Tertib di SMA Negeri 10 Tidore Kepulauan - Irwan Djumat (Universitas Khairun, 2023)
The purposes of this research are: (1) To find out the teacher's role in shaping the disciplinary character of students through school rules at SMA Negeri 10 Tidore Kepulauan City, and (2) To identify factors that influence the teacher's role in shaping the disciplinary character of students through governance. school discipline at SMA Negeri 10 Tidore Islands. The research method used is a case study qualitative research. The subjects of this research were school principals, deputy head of curriculum, deputy head of education, teachers and students. The data collection techniques used were observation, interviews and documentation with data analysis techniques using data reduction, data presentation, and making conclusions. The results of the study show that: (1) The role of the teacher in shaping the disciplined character of students at SMA Negeri 10 Tidore Kepulauan is that the teacher acts as a Role Model for students so that they can be used as an example in life both at school and in society. In addition, the attitude and obedience of the teacher can be emulated by students in order to familiarize students to come to school on time, dress neatly, and not play truant during class hours. Thus the character of discipline can be applied in everyday life. (2) there are 2 factors that influence the disciplinary character of students, namely: (a) Supporting factors, namely the existence of cooperation between teachers and parents of students as the key to success in shaping the disciplinary character of students and the teacher's firmness in carrying out action will affect the disciplined character of students in school; (b) Inhibiting factors, namely lack of self-awareness to be disciplined,as well as a lack of understanding of the disciplinary attitude that is applied in schools